If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 10g + 180 = 3g + 54 Reorder the terms: 180 + 10g = 3g + 54 Reorder the terms: 180 + 10g = 54 + 3g Solving 180 + 10g = 54 + 3g Solving for variable 'g'. Move all terms containing g to the left, all other terms to the right. Add '-3g' to each side of the equation. 180 + 10g + -3g = 54 + 3g + -3g Combine like terms: 10g + -3g = 7g 180 + 7g = 54 + 3g + -3g Combine like terms: 3g + -3g = 0 180 + 7g = 54 + 0 180 + 7g = 54 Add '-180' to each side of the equation. 180 + -180 + 7g = 54 + -180 Combine like terms: 180 + -180 = 0 0 + 7g = 54 + -180 7g = 54 + -180 Combine like terms: 54 + -180 = -126 7g = -126 Divide each side by '7'. g = -18 Simplifying g = -18
| yr+5n=r-6h | | 6(x-1)-x=22-2x | | 40z^2+12-12=0 | | 6x-9=24x+3 | | V-7v=12 | | 15=4(x-3)-(x-9) | | 9=-5n+1+3 | | 4x^2-4x+7x-7=2x-1 | | -4+9(6y+3)=(4y-5)-4 | | 4(x-5)+12=8 | | 32x+4y=0 | | f(x)=50cos(7*(x^6)) | | (x+1)(3x+1)=96x^2 | | 16+5(6c-3)= | | x(x+1)=x(x+1)+5 | | 5ab+8ab= | | 2[7-(-4x-5)]=32x+54 | | 5x+4x+4=x+6x+16 | | T=(7+RS) | | T=(7+RS)forS | | -8+5u=-33 | | 8x+a-12=4x-13-5x | | 5t(9t+4)=0 | | s=4k+4 | | 8t+6=6+7t | | (4z+5)(3-z)=0 | | 13x+24x-31x=144 | | 7y+2=6y-2 | | 3x^2-12x-180=0 | | 3y+8=2y-6 | | 2x^2-6x+14=0 | | 3x^7-243=0 |